Male reproductive toxicity studies of Orthosiphon stamineus aqueous extract in Sprague Dawley rats - Muhammad, Hussin; Omar, Maizatul Hasyima; Md Isa, Muhammad Lokman; Abdullah Thani, Nur Syimah Izzah; Ibnu Rasid, Elda Nurafnie; Awang, Norizah (AkiNik Publications, 2018)
A dose-response study was designed to assess toxicity effects of standardized O. stamineus aqueous extract (OSAE) in adult male Sprague Dawley rats via oral gavage for 60 days. Animals were observed for clinical signs. Body weight gain, food and water consumption and reproductive performance were measured. Animals were sacrificed and blood samples were withdrawn for hematological analysis. Vital and reproductive organs weight, sperm concentration and morphology were collected and evaluated. All animals survived and did not show signs of toxicity. No significant changes on food and water uptake, body and organs weight in all groups. The number of implantation, sperm concentrations, morphology, resorptions and lives fetuses was not statistically significant. Levels of red blood cells, haematocrit, haemoglobin and platelet were significantly higher in rats received 2000mg/kg body weight of extract. The OSAE did not cause toxicity effects, rather, it stimulate erythropoiesis in rats and need further investigation.